Impacto do estresse térmico e de CO2 no crescimento inicial e na fisiologia do meloeiro - Carvalho, Cristhyan Alexandre Carcia de (Universidade Federal Rural do Semi-Árido, 2015)
The survey was conducted in Embrapa tropical agribusiness, in Fortaleza, Ceará, and divided into three separate experiments carried out to evaluate the effects caused by heat stress (Experiments I and II) and by combining temperature and high CO2 concentration (Experiment III) on the growth, physiology, biochemistry and flowering hybrid yellow melon "Goldex" grown in the greenhouse. In all three experiments, the design was completely randomized, the two first were made up of 4 treatments and 8 repetitions and the third was in a 2x2 factorial design with 8 replications. In the experiments I and II, plants were placed in germination chambers with different temperatures (30, 34, 38 and 42 °C), simulating a heat stress. However, in the second experiment, the plants were removed from the chambers at 18 DAT and forwarded to a greenhouse up reaching the flowering phase. In the experiment III, the plants were placed in germination chambers and subjected to treatment 34 °C; 34 °C+900 ppm CO2; 42 °C and 42 °C+900 ppm CO2. In the first experiment, it was found in most of the variables that at least one assessment showed significant differences between treatments, which is not observed for stem diameter and fructose. Plant height, leaf number (NF), leaf area (LA), sucrose and fresh and dry shoot and root (MFA, MSA, MFR and MSR) were negatively impacted by temperature 42 °C. For chlorophyll and gas exchange, despite significant differences between treatments of positive or negative trends, were observed variables. Glucose was positively influenced by the temperatures of 38 and 42°C. In the second trial, there was no significant difference between treatments in the variables except the stem diameter. Plant height, NC, AF and fresh and dry shoot and root mass were negatively impacted by a temperature of 42 °C. Chlorophyll and gas exchange showed significant differences between treatments, however, there was no trend, positive or negative, of the variables in the time periods. The flowering was influenced by the treatments, because of the higher temperature, the later the beginning of this phase is observed. In the experiment III, plant height and stem diameter at 7; 14 e 23 DAT significant differences between the temperatures, concentrations of CO2 and interaction entres them, however, the same result was observed on analysis at 0 DAT fact also checked for the trunk diameter at 23 different concentrations in the DAT CO2. NF to 14 e 23 DAT and the AF and fresh and dry shoot were significantly influenced by factors and interaction entres them. Chlorophyll revealed significant differences only between the temperatures at 7 DAT. Already 14 DAT, there were no significant differences of the factors and interaction between them, at 23 DAT significant differences existed in temperatures and interaction of temperature and CO2. Gas exchange were not affected by temperature, and no interaction between factors at 14 DAT, still the same resource, the CO2 enrichment decreased gs and Ci/Cref not influencing the A and E. Have at 21 DAT, the responses were quite different, and the gas and suffered the effects of temperature, CO2 and the interaction between them. While for Ci/Cref and A were not observed significant effects of the factors nor its interaction with the exception of the increase in the in plants under elevated temperature with or without enrichment of CO2, an effect that was also observed in the gas and the leaves and subjected to 42 ºC + 900 ppm de CO2. The Fv/Fm and F0 were influenced only by temperature. Already Fm and qP suffered no effects of the factors nor the interaction between them. The qN showed significant differences for both factors, with no significant effect only the interaction between them. The ETR was affected by concentrations of CO2 and interaction of temperature and CO2. It follows that the melon subjected to high temperatures (38 and 42 °C) up to 24 days after transplanting showed lower growth. This fact was also observed when plants were subjected to initial thermal stress with 42 °C temperature, with a negative effect also on flowering, slowing within 10 days compared to the temperature of 30 °C. The melon showed further growth in plants under the combination of 34 °C+900 ppm CO2 and lower under high temperature, enriched or not CO2. Most physiological analysis of gas exchange and chlorophyll fluorescence were not affected by treatments
Impact of heat stress and CO2 on the initial growth and physiology of melon
Keywords: Cucumis melo L .; Greenhouse gases; Photosynthetic metabolism; Climate change; fluorescence; Cucumis melo L.; Gases de efeito estufa; Metabolismo fotossintético; Mudanças climáticas; Fluorescência; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA